Analysis of the Zero-Missing Phenomenon on Mixed Overhead-Underground Cables in 220 kV Transmission Lines - Pham, Thanh Chung; Tran, Van Top (Smart Systems and Devices, 2025)
The paper investigates the dynamic behavior of a 220 kV mixed overhead-underground transmission line compensated with a shunt reactor, with a focus on the current zero-missing phenomenon and switching overvoltages. The zero-missing phenomenon, a condition in which the current through the circuit breaker fails to reach zero, can affect breaker operation and system stability, particularly in shunt-compensated systems. Key factors influencing this issue include cable length, cable configuration, reactive power compensation, and switching strategies. Using EMTP/ATP simulations based on a real grid model, the study evaluates various mitigation strategies for the zero-missing phenomenon, such as pre-insertion resistors, compensation ratios, and connections to high-power loads. Transient overvoltages on cable cores and sheaths during switching operations are also analyzed.